Apache Hadoop 3 Quick Start Guide : Learn about Big Data Processing and Analytics. - Vijay Karambelkar, Hrishikesh (Packt Publishing Ltd, 2018)
Apache Hadoop is a widely used distributed data platform. It enables large datasets to be efficiently processed instead of using one large computer to store and process the data. This book will get you started with the Hadoop ecosystem, and introduce you to the main technical topics such as MapReduce, YARN and HDFS.